What Do We Know About Variance in Accounting Profitability? - McGahan, Anita M.; Porter, Michael E. (Management Science, 2002)
In this paper, we analyze the variance of accounting profitability among a broad cross-section of forms in the American economy from 1981 to 1994. The purpose of the analysis is to identify the importance of year, industry, corporate-parent, and business-specific effects on accounting profitability among operating businesses across sectors. The findings indicate that industry and corporate-parent effects are important and related to one another. As expected, business-specific effects, which arise from competitive positioning and other factors, have a large influence on performance. The analysis reconciles the results of previous studies by exploring differences in method and data. We also identify the broad contributions and limitations of the research, and suggest avenues for further study. New approaches are necessary to generate significant insights about the relationships between industry, corporate-parent, and business influences on firm profitability.